PENGARUH RETURN ON EQUITY DAN EARNING PER SHARE TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rudiyanto Rudiyanto; Mike Mega Rahayu; Aditia Firmansah (Sekolah Tinggi Ilmu Ekonomi La Tansa Mashiro, 2020)
This study aims to find out ROE and EPS can affect the House of Representatives in LQ 45 companies listed on the Indonesia Stock Exchange (IDX). The method used in this research is quantitative descriptive research method. The population used is all LQ 45 companies listed on the Indonesia Stofck Exchange (IDX) using purposive sampling method. Collecting data obtained through secondary data. Data analysis techniques used in this study are Classical Assumption Test consisting of (Data Normality Test, Multicollonierity Test, Heterocedasticity Test, and Autocorrelation Test), Multiple Linear Regression Analysis Test, Correlation Analysis Test, Determination Coefficient Test, and Hypothesis Test consisting of Test T statistics and Test Statistics f.Research results from SPSS version 20 shows the results of multiple linear regression analysis stating Y = 4.863 + 0.903 X1 + 0.055 X2 means that each additional value of Rp. 1 ROE can increase the DPR by 0.903 and each additional value of Rp. 1 EPS can increase the DPR by 0.055. The results showed that testing the partial correlation of ROE variables with the DPR has a value of 0.026 indicating a low relationship and EPS variables with the DPR has a value of 0.092 indicating a very low relationship and simultaneous correlation testing of ROE and EPS variables with the DPR has a close value of 0.438 shows enough connection. The test results of the coefficient of determination have a value of 19.2% which means that it can be seen that the DPR is influenced by 19.2% and the remaining 70.8% is influenced by other variables. According to the t-test result of 2.989 t table 2.005 H1 is accepted by having a significant value of 0.004 0.05 H0 is rejected meaning that ROE has a significant influence on the DPR and the t test result is 2.549 t table 2.005 H1 is accepted by having a significant value of 0.014 0.05 H0 is rejected meaning EPS has a significant influence on the DPR. The result of the f test shows that the count of 6.163 ftabel 3.18 H1 is accepted by having a significance value of 0.004 0.05 H0 rejected meaning that ROE and EPS have a significant influence on the DPR.